Pengaruh Locus Of Control, Kompleksitas Tugas, Self Efficacy Dan Persepsi Etis Terhadap Audit JudgementStudi Pada Kantor Akuntan Publik Di Kota Surakarta Dan Semarang - Dewi, Ricca Rosalina, Dra. Rina Trisnawati, Ak, M.Si, Ph (2016)
Auditor is a professional whose job carrying out an audit of the entity's financial statements and draw conclusions. Audit judgement a significant influence on final conclusion, so that will affect the opinion will be issued by the auditor. Research objective to determine the effect of locus of control, complexity of the task, self efficacy and ethical perseption influence on audit judgement. The method used was survey method with questionnaire data collection techniques. The sample in this study was the auditors who work in KAP firm in Surakarta and Semarang. Analytical techniques used multiple linear analysis. The results showed that: (a) the locus of control effect on audit judgement , the t test obtained the significance value 0.000 < 0.05 (b) complexity of the task effect on audit judgement, the t test obtained the significance value 0.025 < 0.05 (c) self efficacy effect on audit judgement, the t test obtained the significance value 0.046 < 0.05 (d) perseption influence effect on audit judgement, the t test obtained the significance value 0.020 < 0.05